META-ANALYSIS OF THE INQUIRY LEARNING LEARNING MODEL IN IMPROVING CRITICAL THINKING ABILITY OF FIFTH-GRADE ELEMENTARY SCHOOL STUDENTS - Khofi, Mohammad Bilutfikal; Suheri (International Conference on Humanity Education and Society (ICHES), 2024)
The purpose of this research is to re-analyze the use of the inquiry learning model to improve the critical thinking skills of fifth-grade elementary students. This type of research uses meta-analysis research. This research begins by formulating a research problem and then searching for relevant journals or articles to analyze. The data collection technique uses non-tests by searching and browsing relevant journals or articles through Google Scholar. The results of this research showed that the learning model could improve the critical thinking skills of fifth-grade students, ranging from the lowest 9.66% to the highest 36.54%, with an average increase of 23.17%. Based on the results of calculating the effect size for the 10 journals or articles studied, an effect size of d = 3.41 was obtained, which means d = 3.41 > 1.30. It can be concluded that the positive influence is in the very high category. This means that the inquiry learning model has a very high influence on improving the critical thinking skills of fifth-grade students